2018
DOI: 10.1002/ecy.2194
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific trait variation and the leaf economics spectrum across resource gradients and levels of organization

Abstract: Understanding patterns of functional trait variation across environmental gradients offers an opportunity to increase inference in the mechanistic causes of plant community assembly. The leaf economics spectrum (LES) predicts global tradeoffs in leaf traits and trait-environment relationships, but few studies have examined whether these predictions hold across different levels of organization, particularly within species. Here, we asked (1) whether the main assumptions of the LES (expected trait relationships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
89
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(105 citation statements)
references
References 25 publications
10
89
1
1
Order By: Relevance
“…Specifically, species that occurred across a wide range of light environments had high ITV in leaf N concentration, and species broadly distributed along the soil P availability gradient had high ITV in leaf N and P. Importantly, we found these positive relationships between niche breadth and ITV by comparing species’ ITV measured across a common set of environments. Research conducted in these southern hemisphere cool temperate rainforests thus far (Lusk , Fajardo and Siefert , Peltzer and Wardle ) has commonly focused on light availability as the limiting factor, especially, for regeneration, but here we show that soil N and P availability had a strong positive relationship with leaf trait variation, indicating that multiple environmental filters drive regeneration dynamics (see also Lusk and Laughlin , Fajardo and Siefert ). Although some studies have found that N is the most limiting nutrient in soils of temperate rainforests in southern Chile (Huygens et al ), the volcanic origin of these soils makes them very poor in available P for plants (large amount of allophane and sesquioxide in the soil, which have a high phosphate‐fixing capacity, making P not readily available for plants) (Fajardo and Piper ).…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…Specifically, species that occurred across a wide range of light environments had high ITV in leaf N concentration, and species broadly distributed along the soil P availability gradient had high ITV in leaf N and P. Importantly, we found these positive relationships between niche breadth and ITV by comparing species’ ITV measured across a common set of environments. Research conducted in these southern hemisphere cool temperate rainforests thus far (Lusk , Fajardo and Siefert , Peltzer and Wardle ) has commonly focused on light availability as the limiting factor, especially, for regeneration, but here we show that soil N and P availability had a strong positive relationship with leaf trait variation, indicating that multiple environmental filters drive regeneration dynamics (see also Lusk and Laughlin , Fajardo and Siefert ). Although some studies have found that N is the most limiting nutrient in soils of temperate rainforests in southern Chile (Huygens et al ), the volcanic origin of these soils makes them very poor in available P for plants (large amount of allophane and sesquioxide in the soil, which have a high phosphate‐fixing capacity, making P not readily available for plants) (Fajardo and Piper ).…”
Section: Discussionmentioning
confidence: 49%
“…In temperate rainforests of southern Chile, where as many as 25 woody species per hectare can co‐occur within forest communities, species can be found in a variety of local environmental conditions, from deep shade to tree‐fall canopy gaps (Veblen 1985, Lusk , Fajardo and Siefert , ), and from spots with poor to rich nutrient availability. Given these apparent strong environmental gradients, we expected that species achieving high local abundance would be those that could tolerate a wide range of environments by adjusting their trait values to local conditions (Darwin 1859, Sides et al ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As with all such largescale patterns, the question emerges of how it evolved, and whether within-species patterns are consistent with across-species patterns. These studies have largely taken a phenotypic approach assessing within vs. between species trait associations, typically via field sampling within and between plant communities (Funk and Cornwell 2013, Niinemets 2015, Fajardo and Siefert 2018. The authors concluded that constraints are thus unlikely the driver of the LES, but rather selection for and against particular trait combinations is more likely responsible for the pattern across species.…”
Section: Evolutionary Ecology Of the Leaf Economics Spectrummentioning
confidence: 99%